Sensitivity comparison between rapid one-step test strip and ELISA methods in detection of HBsAg among selected chronic liver disease patients in University of Calabar Teaching hospital, Calabar, Nigeria - Okpokam, D.C.; Kooffreh-Ada, M.; Okhormhe, Z.A.; Ernest, N. A.; Nna, V. U. (Asian Journal of Medical Sciences, 2015)
Background: Hepatitis B virus (HBV) is the eloquent hepatic infection that leads to hepatocellular carcinoma. This study aims to determine the frequency of HBV by screening selected chronic liver disease (CLD) patients alongside few apparently healthy subjects who might be carriers and pose a high risk in HBV transmission. This study also aims to compare the sensitivity between two diagnostic tests; one step rapid test strip device and Enzyme Linked Immunosorbent Assay (ELISA). Methodology: Serum of 111 subjects comprising of 76 CLD patients and 35 apparently healthy (control) subjects was screened for Hepatitis B surface Antigen (HBsAg). Results: Sero-positivity of the two methods of detecting HBsAg was higher in age group 26-35 years and the male folk was found higher in number than the females. The seropositivity of HBV was 28.8% and 81.1% while seronegativity was 71.2% and 18.9% for rapid test strip test device and ELISA test methods, respectively. All the CLD patients 76(100%) and 14 out of 35 of the apparently healthy subjects was positive for ELISA test method. Conclusion: In conclusion, comparing the two methods, ELISA test is more sensitive than one step rapid test strip device for detecting HBsAg in University of Calabar Teaching Hospital, Nigeria.Therefore, we recommend strongly, thatELISA method be used to confi rm test results obtained from the one step rapid test strip,when screen for CLD. DOI: http://dx.doi.org/10.3126/ajms.v6i5.11851 Asian Journal of Medical Sciences Vol.6(5) 2015 56-60